Decolorization of Palm Oil Mill Effluent by Klebsiella Pneumonia ABZ11: Remediation Efficacy and Statistical Optimization of Treatment Conditions - Abdulsalam, Mohammed; Man, Hasfalina Che; Abidin, Zurina Zainal; Yunos, Khairul Faezah; Idris, Aida Isma (Frontiers in Microbiology, 2020)
Colourants contained in palm oil mill effluent (POME) are recalcitrant and carcinogenic in nature. The commonly applied ponding treatment methods have been reported inefficient for remediating the concentration of the colourants before discharge. The need for sustainable and efficient treatment technique is crucial in order to preserve the environment. In this view, this study reported the first attempt to decolourize POME using a proliferate Klebsiella Pneumonia ABZ11 at varied inoculum sizes of 5-25 % (v/v), initial colour concentration (650-2600 ADMI) and treatment time of 5-40 h. The treatment conditions were optimized using Response Surface Methodology. At optimal conditions of 20 % (v/v) inoculum size, initial-colour concentration of 2600ADMI, initial pH of 7 and 35 h treatment retention time, over 80.40 % colour removal was achieved with insignificant disparity compared with the model predicted value of 81.538 %. Also, the Monod model excellently described the decolourization kinetic process with 0.9214 coefficient of correlation (R2), and the calculated maximum growth (μ_max) and half-saturation constant (Ks) were 7.023 d-1 and 340.569 ADMI.d-1, respectively. This study revealed that the Klebsiella Pneumonia ABZ11 was highly prolific and such feature may favours a synergistic biodegradation process.